Determination of the Waterway Parameters as a Component of Safety Management System - Andrzej Bąk; Paweł Zalewski (Applied Sciences, 2021)
This article presents the use of a computer application codenamed “NEPTUN” to ascertain the waterway parameters of the modernised Świnoujście–Szczecin waterway. The designed program calculates the individual risks in selected sections of the fairway depending on the input data, including the parameters of the ship, available water area, and positioning methods. The collected data used for analyses in individual modules are stored in a SQL server of shared access. Vector electronic navigation charts of S-57 standard specification are used as the cartographic background. The width of the waterway is calculated by means of the method developed on the basis of the modified PIANC guidelines. The main goal of the research is to prove and demonstrate that the designed software would directly increase the navigation safety level of the Świnoujście–Szczecin fairway and indicate the optimal positioning methods in various navigation circumstances.